How to inspire innovation through the world without the web. Issue 54 (October 2015) - Anso, Martin; Kuppa, Smitha; Mardolker, Samy; Salvage, Tony; Jeffs, David; Tan, Christine
Abstract : Brands can enhance consumer experiences by leveraging the human aspects of life endangered by digital technology.